The Principle of Dwi Tunggal Siwa-Buddha in Bahung Tringan Community - I Gede Swantana (UHN IGB Sugriwa Denpasar, 2018)
This article descriptively describes the principle of unification of Siwa-Buddha which was publicized by theBahung Tringan community in Karangasem, Bali. At first, Shiva and Buddha were separate religions whenit came to the archipelago, Indonesia. Over time, in the political’s influence of the state, this religion is parallel, it is Shiva and Buddha are sole (singular). This is an early form of Siwa-Buddha unification. However,in this contemporary age, after it took off about 500 years after the Majapahit’s collapse, the Shiva-Buddhaprinciple was started to discuss and practise again. The Bahung Tringan community practises this as a meditation technique. Bahung Tringan’s people considered that the Principle of the Dwi Tunggal Shiva-Buddhais a theological principle related to the level of achievement of a sadhaka (spiritual aspirant). This principleworks in a process called spirit process. The way of the Dwi Tunggal Siwa-Buddha works is to follow a process named tantra, it is an encounter of the positive and negative aspects of the mind that produce a vacuum.From this vacuum raised Jnana, and this Jnana drives the spirit to reunite with Sangkan Paraning Dumadi.